Skeptical Theism and Enlightenment Thinkers in Tracing Epistemological Humility - Michael Yurievich Kuznetsov (Jurnal Multidisiplin Ibrahimy, 2025)
This study examines the origins and development of skeptical theism a philosophical position that reconciles belief in God with the recognition of human cognitive limitations in understanding divine providence, particularly regarding the problem of evil. While skeptical theism formally emerged in modern philosophy, its foundations can be traced to Enlightenment thinkers who grappled with the boundaries of human reason and faith. Through historical-philosophical and analytical methods, this work analyzes the contributions of six key figures John Locke, Gottfried Wilhelm Leibniz, David Hume, Denis Diderot, Jean-Jacques Rousseau, and Immanuel Kant demonstrating how their diverse perspectives shaped the epistemological framework of skeptical theism. Locke’s empiricism and Leibniz’s rational theodicy laid early groundwork, while Hume’s radical skepticism and Diderot’s materialism, though atheistic, inadvertently reinforced the notion of cognitive limits. Rousseau’s natural religion and Kant’s critical philosophy further refined the balance between faith and reason, emphasizing the inscrutability of divine will. The study highlights how these thinkers, whether theistic or not, collectively advanced the principle of epistemological humility a core tenet of skeptical theism. By offering a comparative analysis rarely found in existing literature, this essay bridges historical and contemporary debates on theodicy, divine hiddenness, and the rationality of religious belief. Its findings are relevant to philosophy of religion, epistemology, and interdisciplinary studies, providing a foundation for further research on skeptical theism’s dialogue with modern movements like reformed epistemology.